Rising Glaucoma Burden in Pakistan: A Wake-up Call for Nationwide screening? N/A - Sana Kazmi; Adina Jabeen; Gul, Rabbia (Journal of the Pakistan Medical Association, 2022)
A significant rise of 55% in blindness and vision impairment in Pakistan has been reported over the last few decades, with blindness being the third most common eye disorder in the country1. Among its different causes one of the leading cause is glaucoma, with an age standardized prevalence of 0.14 million1. Glaucoma comprises a group of diseases that can result in irreversible damage to optic nerves and vision loss, it affects 3.1 million people around the world2. The occurrence of glaucoma in elderly has increased in the last few decades and a significant rise in the burden of eye diseases, including glaucoma, in Pakistan, is predicted by the year 20251. Primary open-angle glaucoma is the most common form of glaucoma; it is asymptomatic in the early stages and patients usually present after significant damage to nerve fibres. One of the major risk factors for this disease is advancing age, being most prevalent in people over 40 years of age1. Moreover, a study conducted in Pakistan reported a high prevalence of primary open angle glaucoma in individuals over the age of 503. While glaucoma is one of the leading causes of blindness, the risk of blindness posed may be profoundly diminished with early diagnosis; a study suggests a marked decrease in blindness due to glaucoma owing to early diagnoses4. In Pakistan, however, health seeking behaviour is already suboptimal. Additionally, a significant lack of awareness about glaucoma has also been reported in Pakistan, specifically in populations over the age of 455, which is the age group at the greatest risk of development of glaucoma. Proper access to eye health has been associated with employment prospects and economic productivity, especially in developing countries like Pakistan2, while loss of vision can lead to poor quality of life, especially in a country with very few options for meeting the needs of those who are visually impaired, leaving them with limited options for employment, hence forcing them to be dependent on others. This can collectively have a negative impact on a developing nation’s economy. Considering the aforementioned factors, it goes without saying how incredibly imperative it is to devise a thorough strategic plan for screening, prevention and diagnosis, coupled with necessary awareness programmes to curb and reduce the instances of glaucoma and glaucoma-associated complications as a whole.